في مهب الحداثة: دراسة لأوجه التشابه بين اليهودية الإصلاحية بألمانيا والاتجاه التغريبي في مصر In the windward of modernity: A study of the similarities of Jewish Reformism in Germany and westernizing trend in Egypt - محمد دأود (Noor Amali bin Mohd. Daud), نور أمالي (At-Tajdid - Intellectual Refereed Journal, 2009)
Abstract Western modernity has challenged religious thought in various ways. This article deals with the issue of religious thought in encountering Western modernity with particular emphasis on similarities between Reform Judaism inGermanyand modernist Muslim thinkers inEgyptin their encounter with modernity. The study reveals that there are three common characteristics shared between these two intellectual responses to the challenges of modernity, as follows, (i) promoting the idea of total assimilation in Western modernity; (ii) belittlement of religious and cultural tradition and, (iii) returning back to the original convictions of religion, acknowledging its significance and denouncing the destructive elements of Western modernity. مستخلص البحث لقد تحدت الحداثة الغربية الفكر الديني في جوانب متعددة. تعالج هذه المقالة إشكالية الفكر الديني في مواجهة الحداثة الغربية بالتركيز على أوجه التشابه بين تجربتي كل من اليهودية الإصلاحية في ألمانيا والاتجاه التغريبي في مصرفي تعاطيهما مع الحداثة. وقد أثبتت الدراسة بأن ثمة خصائص ثلاثًا مشتركة في استجابات كل من الاتجاهين لتحديات الحداثة وهي تتمثل في النقاط الآتية: أولاها: ترويج فكرة الاستسلام الكلي لمعطيات الحداثة الغربية، وثانيها: الحط من قدر الموروثات الدينية التقليدية والتقليل من شأنها والقيام بدعوة إلى التحول الكلي عنها، وثالثها: العودة إلى الإيمان الديني والإقرار بفعالية الموروثات الدينية التقليدية من جديد وبداية كشف وإظهار العناصر المدمرة للحداثة الغربية.